TRANSFORMING FINANCIAL BEHAVIOR AND GOVERNANCE THROUGH COMMUNITY-BASED EDUCATION: LESSONS FROM YOUTH AND MSMES IN INDONESIA - Arif Ahmad Fadilah; Achmad Fauzi; Solihin Solihin (Community Services and Social Work Bulletin, 2025)
Financial literacy is a critical life skill that enables individuals to make informed decisions, develop financial resilience, and contribute to sustainable economic growth. However, many youths and micro, small, and medium enterprises (MSMEs) in developing countries continue to face persistent financial literacy gaps that limit their economic empowerment and participation in the formal economy. This community-based engagement study aims to strengthen financial capabilities among youth and MSME actors through a collaborative education model that integrates financial literacy training, practical learning experiences, and digital financial adoption. A qualitative descriptive method was employed, involving in-depth interviews, observations, and documentation with youth aged 15–22 and MSME owners in semi-urban communities. The findings indicate that the program effectively enhanced youth understanding of budgeting, saving behavior, and responsible use of digital financial services. For MSMEs, improvements were observed in bookkeeping practices, separation of personal and business finances, and initial adoption of digital financial applications. The initiative not only fostered positive financial behavior change but also strengthened local economic ecosystems through intergenerational knowledge exchange and practice-based learning. The study concludes that collaborative educational interventions play an essential role in advancing financial inclusion, elevating MSME financial management, and supporting community economic sustainability, suggesting the need for continuous and scalable models in similar contexts.